2013
DOI: 10.1097/01.epx.0000431629.28378.c0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of sick building syndrome among office workers

Abstract: SBS was highly prevalent among office workers and was influenced by physical and psychosocial working conditions. Good ventilation, reducing room temperature, effective cleaning routines, providing proper lighting, restricting smoking in the workplace, and improving psychosocial working conditions are important ways to reduce SBS symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Abdel‐Hamid and colleagues revealed the significant positive association of noise with SBS symptoms in a survey of 826 office workers in Egypt . It is similar to the findings of our study in which we found that employees experiencing disturbance from noise reported more often general and ocular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Abdel‐Hamid and colleagues revealed the significant positive association of noise with SBS symptoms in a survey of 826 office workers in Egypt . It is similar to the findings of our study in which we found that employees experiencing disturbance from noise reported more often general and ocular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of an air-conditioned building in Niteroi, Rio de Janeiro, Brazil, Costa and Brickus (2000) concluded that poor individual control of temperature and lighting are associated with increased symptoms. A univariate analysis, performed by Abdel-Hamid et al (2013) at the Faculty of Medicine, Ain Shams University, Cairo, Egypt showed that poor lighting, poor ventilation, lack of sunlight, absence of air currents, high noise, temperature, humidity, environmental tobacco smoke, use of photocopiers, and inadequate office cleaning were statistically associated with SBS symptoms. Building characteristics, such as year of construction and the effect of indoor emissions lead to SBS.…”
Section: Multi-group Interactionsmentioning
confidence: 99%
“…Fourteen articles were reported as cross-sectional studies (Abdel-Hamid, Hakim, Elokda, & Mostafa, 2013;Azuma, Ikeda, Kagi, Yanagi, & Osawa, 2015;Brasche et al, 2004;Glas, Levin, Stenberg, Stenlund, & Sunesson, 2004;Jaakkola, Yang, Ieromnimon, & Jaakkola, 2007;Jung, Liang, Lee, Hsu, & Su, 2014;Kubo et al, 2006;Lim et al, 2015;Lu, Lin, Chen, & Chen, 2015a;Lu et al, 2007;Mendell, Lei-Gomez, Mirer, Seppänen, & Brunner, 2008;Reijula & Sundman-Digert, 2004;Skyberg et al, 2003), three were longitudinal studies (Azuma, Ikeda, Kagi, Yanagi, & Osawa, 2017;Mizoue, Andersson, Reijula, & Fedeli, 2004;Tsai et al, 2012), two were case-control studies (Glas, Stenberg, Stenlund, & Sunesson, 2008, one was a cohort study (Neuner & Seidel, 2006), one was a case report (Nakazawa et al, 2005), one was a systematic review together with epidemiological modelling (Fisk, Mirer, & Mendell, 2009), and one was a cost-benefit study (Fisk, Black, & Brunner, 2011).…”
Section: Types Of Studymentioning
confidence: 99%